Screening for penicillin allergy in obstetric patients to optimize guideline directed therapy - Kayla Godfrey; Deanna McDanel; Kelly Percival; Noelle Bowdler; Donna Santillan; Amy Dowden (Antimicrobial Stewardship & Healthcare Epidemiology)
Abstract